Record current density of 344 A mm−2 at 4.2 K and 17 T in CORC® accelerator magnet cables. (5th April 2016) - van der Laan, D C; Weiss, J D; Noyes, P; Trociewitz, U P; Godeke, A; Abraimov, D; Larbalestier, D C
Abstract: One of the biggest challenges in developing conductor on round core (CORC ® ) magnet cables for use in the next generation of accelerator magnets is raising their engineering current density J E to approach 600 A mm −2 at 20 T, while maintaining their flexibility. One route to increase J E could be to add more RE-Ba2 Cu3 O7− δ coated conductors to the cable, but this would increase the cable size and reduce its flexibility. The preferred route to higher J E is a reduction in diameter of the CORC ® cable, while maintaining the number of tapes wound into the cable. The availability of very thin tapes containing substrates of 30 μ m thickness enabled us to wind a 5.1 mm diameter CORC ® cable from 50 coated conductors, while maintaining a tape critical current I c of about 97% after cabling. The cable I c was 7030 A at 4.2 K in a background field of 17 T, corresponding to a J E of 344 A mm −2, which is the highest performance of any CORC ® cable so far. The magnetic field dependence allowed us to extrapolate the cable performance to 20 T to predict an I c of 5654 A and a J E of 309 A mm −2 . The results clearly show that rapid progress is being made on overcoming the J E hurdle for use of CORC ® cables in the next generation of accelerator magnets. Further optimization of the cable layout will likely increase J E towards 600 A mm −2 at 20 T in the near future, while further reduction in cable size will also make them even more flexible.